In Vitro Evaluation of Sodium Hypochlorite, Chlorhexidine, Propolis, and Calcium Hydroxide Effect on Lipoteichoic-Acid-Induced Proinflammatory Cytokines Production - Luciane Dias de Oliveira; Lara Steffany de Carvalho; Ana Claudia Carvalho Xavier; Felipe Eduardo de Oliveira; Mariella Vieira Pereira Leão; Mariana Gadelho Gimenez Diamantino; Rayana Duarte Khoury; Marcia Carneiro Valera; Cláudio Antonio Talge Carvalho; Amjad Abu Hasna (MDPI AG, 2024)
This study aimed to evaluate the effects of sodium hypochlorite (NaOCl), chlorhexidine (CHX), and the glycolic extract of propolis (GEP) as endodontic irrigants and of calcium hydroxide [Ca(OH)2], CHX, or Ca(OH)2 + CHX as intracanal medications on the capacity of the lipoteichoic acid (LTA) of Enterococcus faecalis in macrophages' proinflammatory cytokines production. Freshly extracted 108 human single-rooted teeth were used in this study. The LTA of E. faecalis was standardized in double-distilled pyrogen-free water (250 µg/mL) and inoculated into the specimens subdivided into nine subgroups (n = 12). Cultures of murine macrophages (RAW 264.7) were treated with 30 µL of each sample collected from root canals and incubated (37 °C, 5% CO2) for 24 h. Lastly, anti-TNF-α, anti-IL-6, anti-IP-10, anti-MIP-1α, anti-G-CSF, and anti-IL-1β DuoSet kits were used to perform an ELISA assay. Data were analyzed using one-way ANOVA and Tukey test (p ≥ 0.05). It was found that 1% NaOCl was the most effective irrigant in reducing the capacity of LTA in cytokines production, followed by 12% GEP and 2% CHX, respectively. Ca(OH)2 + CHX presented the best results when associated with NaOCl or GEP. Thus, NaOCl or GEP associated with Ca(OH)2 + CHX were effective in reducing the capacity of LTA in different macrophages pro-inflammatory cytokines production.